Penentuan Ukuran Batch dan Sequence Optimal Dalam Sistem Produksi Dua Stage - I Wayan Suletra (Performa: Media Ilmiah Teknik Industri, 2006)
This paper extends previous study of batch sizing and sequencing problems in flow line production system. We develop a new model to optimize the batch size and sequence in two-stage production system. The previous study optimizes the same decision variables but for single-stage production system. In this study, stage 1 has one machine and makes a batch of N types of component with different size for each type. Stage 2 also has single assembling facility and assembles those batch of components into a batch of single type of final product. Each type of component has a different setup time and setup cost, and each batch offinal products has constant setup time and constant setup cost. Optimum batch size and optimum sequence will minimize average production cost per unit time.